Efektivitas Suplemen Biji Fenugreek Terhadap Kecukupan Air Susu Ibu Pada Ibu Nifas Hari I - Happy Marthalena Simanungkalit; Rafika Sri P (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2022)
Mothers who breastfeed often issue problems in exclusive breastfeeding, one of the main obstacles is inefficient production of breast milk. This will be a factor in the lack of exclusive breastfeeding support for newborns. One effort that can be done to increase the speed of secretion and milk production is through the use of supplements with the support of fenugreek seeds. The purpose of this study was to determine the effectiveness of fenugreek seed supplements on the adequacy of breast milk in the working area of ​​the Pasir Putih Health Center. The design used in the Quasi experimental study was with a control group using pre test - post test design. The population in this study were all postpartum mothers in the Pasir Putih Health Center and a large sample of 11 people each.The statistical test used in this study is the Chi-Square test. Statistical test results obtained the value of P Value 0.010 with the provisions of the value of p <0.05, then the P Value <a so that it can be concluded that fenugreek seed supplements are effective against the adequacy of breast milk. Therefore, health workers can improve service to breastfeeding mothers by providing assistance in expediting milk production by taking supplements of fenugreek seeds